Colors in nature - Jones, Christianne C (North Mankato, Minnesota Pebble, a Capstone imprint, 2022)
"From vibrant red flowers and clear blue skies to big brown trees and buzzing yellow bees, color is everywhere in nature. Interactive, rhyming text and bright photographs bring the bold colors of nature to young readers in this picture book"--
Ages 5-8
Grades K-1
111244
Keywords: Color in nature -- Juvenile literature; Colors -- Juvenile literature; Juvenile works